TINJAUAN KEPUASAN PASIEN TERHADAP PELAYANAN PETUGAS PENDAFTARAN RAWAT JALAN DI RUMAH SAKIT BHAKTI KARTINI TAHUN 2021 - Anisa Dyah Irawati; Puteri Fannya; Laela Indawati; Nanda Aula Rumana (Lembaga Pengembangan Kinerja Dosen, 2022)
Patient satisfaction is the same as the results of the assessment in the form of emotional responses ranging from feelings of pleasure or satisfaction obtained by patients because of the fulfillment of expectations or desires in using or receiving services. The impact of low patient satisfaction on services at outpatient registration is that it can cause a decrease in the quality of hospital services and result in a decrease in patient visits at the hospital. The purpose of this study was to determine the level of patient satisfaction with the services of outpatient registration officers at Bhakti Kartini Hospital. The method used is descriptive quantitative by distributing questionnaires to 106 respondents measured on 5 dimensions of service quality. From these studies it is known that the percentage of satisfaction to the dimensions of reliability 81.1%, responsiveness 84.9%, assurance 84%, empathy 79.2%, and the physical tangibles 82.1%. Thus, it is known that the level of patient satisfaction with the services of outpatient registration officers at Bhakti Kartini Hospital is 83% and those who are dissatisfied are 17%. Based on the results, the level of satisfaction obtained has not yet reached the minimum hospital service standard that has been set by Kepmenkes 129 in 2008 which is at least 90%.